Longitudinal associations between lead dose and renal function in lead workers - Weaver, Virginia M. (2008)
BACKGROUND: Existing research on the lead dose range associated with nephrotoxicity in the occupational setting is inconsistent and primarily cross-sectional in design. OBJECTIVE: To determine if lead dose predicts change in renal function in a large population of current and former lead workers. METHODS: Three evaluations were performed between 1997 and 2001. Lead dose was assessed with blood and tibia lead. Renal outcomes included blood urea nitrogen, serum creatinine, and calculated creatinine clearance. We used generalized estimating equations to model change in renal function between each evaluation in relation to tibia lead at the beginning of each follow-up period and concurrent change in blood lead, while adjusting for baseline lead dose and other covariates. RESULTS: At baseline, mean (SD) age and duration of occupational lead exposure were 42.0 (9.3) and 8.8 (6.3) years, respectively, in 537 current and former lead workers followed over a mean of 2.1 years. Mean (SD) blood and tibia lead were 31.3 (14.4) μg/dL and 35.0 (37.8) μg/g bone mineral, respectively. Women (25.9%) were older and more likely to be former lead workers than men. In males, serum creatinine decreased and calculated creatinine clearance increased over the course of the study. Mean blood lead was not significantly different between evaluations 1 and 3 in either sex, however, tibia lead decreased in women. Blood and tibia lead were significantly associated with change in renal function. In males, serum creatinine decreases and calculated creatinine clearance increases were greatest in participants whose blood lead declined. CONCLUSIONS: Both acute and chronic occupational lead dose measures were associated with change in renal function measures prospectively.